Analisis Sektor Ekonomi Provinsi Gorontalo Tahun 2017-2022 - Olii, Rizky Rahmadiansyah Putri; Sudirman, Sudirman; Halid, Risca Marsanti (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
Indonesia, as an archipelago, has different regional characteristics, so the problem of regional inequality cannot be avoided. The central government authorizes local governments to develop the potential of the region so that each region is required to be able to independently improve its economy. Gorontalo province, as a province of expansion in 2000, is in a strategic location that has great potential in the agricultural sector, as well as in mariculture an agriculture. The research objective is to determine the condition of economic inequality in Gorontalo province and the leading sectors in each district/city of Gorontalo province. Using time series data from 2017-2022, inequality is analyzed using the Williamson Index (IW), and to determine leading sectors, location quotient (LQ) analysis is used. The results show that the level of inequality in Gorontalo province is close to zero, which means that the condition of the level of income and welfare of the population is evenly distributed because the majority of population employment is still dominated by the agriculture, sector, which is the leading sector in Gorontalo, Boalemo, and North Gorontalo districts, and the trade sector, which is the leading sector in Boalemo and Bonebolango districts